Biochemical properties of sheep colostrum and its potential benefits for lamb survival: a review - Umar Farooq; Sohail Ahmed; Guiqiong Liu; Xunping Jiang; Huiguo Yang; Jianping Ding; Mehboob Ali (Animal Biotechnology)
Colostrum is the initial secretion of the mammary glands following parturition, which offers main food, protection, and biological active substances for the new born. The most threatening episode of neonate’s life is the initial two weeks after birth. This period is associated with high neonatal mortality and morbidity. These worthwhile losses lead to a poor prolificacy rate, low profitability, and ultimately poor performance in animal production. Hence, both diseases and mortality cause valuable losses in terms of production and economic losses. The survival of neonate is correlated with their immune status and passive immune transfer (PIT). Colostrum provides the primary source of nutrition and immunity (PIT) that protects neonates against infections. It must be given as soon as possible after birth since its immunoglobulins are absorbed within the first 16–27 hours after birth, ideally within 2–4 hours. As a result, immunoglobulin (PIT) is the most important component of distressing infectious immunity, and a passable concentration of immunoglobulin in the blood of newborn lambs is linked to their health and survival rate. In this review, we summarized the importance of colostrum in early life and its association with neonatal lamb’s survival, profitability and productivity of sheep farming.